Social Integration in Newspaper Reporting: The Coverage of Vision School By Three Malaysian Dailies - Yang, Nicole Lai Fong (2003)
This research was conducted to examine the coverage on Vision School by the different language dailies to better understand their role in promoting social integration. The daily newspaper with the largest circulation was chosen from the three main language streams. The three dailies chosen were Utusan MalaYSia, a daily in Bahasa Malaysia or the national language, The Star, an English language daily, and Sin Chew Jit Poh, a Chinese language daily. Content analysis was used in this research. A sub-sample of a "constructed week" was created for an indepth analysis and a total of 68 news items were qualified for an analysis in this study. The data were analyzed using the Statistical Package for Social Science (SPSS). Frequencies and percentages were employed in descriptive analysis. This study discovered that three of the dailies did not play an active role in promoting social integration in their coverage of Vision School. This study found very little evidence that the dailies tried to provide collective representations, which is the social symbols to promote cohesion and solidarity. The coverage by the three dailies also did not increase the degree of consensus or common assent that is necessary to sustain an integrated social system. This study recommended that the Vision School issue should be given equal coverage by all the major language newspapers because it is not an issue of race and ethnicity but of education. All newspapers must provide neutral coverage on the Vision School issue irrespective of the language of the newspapers because the function of the press is to inform and not to judge. This study also recommended that all news articles should aim at promoting social integration , intercultural understanding and tolerance. Newspapers should utilize and develop the specific potentialities of media to offer experiences and stimulate the imagination, thus affording opportunities for empathy, involvement and amusement.